Corporate financial structure of South Korea after Asian financial crisis: The chaebol experience - Jiyoung Kim (Journal of Economic Structures, 2017)
The chaebol, a South Korean form of business conglomerate, has been a key factor in the country's economic growth. In this study, the chaebol sector is added to the asset-liability matrix derived from a flow-of-funds analysis in order to explain the role of the chaebol in the Korean financial system. We find that the power-of-dispersion indices in the asset-oriented system differ between the chaebol and other private corporations. Between 1987 and 2002, the former has increased while the latter has declined. In the case of the chaebol, excess liabilities were reduced, while investments in financial assets were increased. This tendency led to an increase in the power-of-dispersion index in this asset-oriented system. Our previous research found a decrease in this index for the private sector in Korea. However, the index increased for chaebol when the private sector is divided into the chaebol and small-/medium-sized corporations in this paper. These results point to a greater concentration of economic power in the chaebol in the Korean financial market.
Keywords: G30; O16; C67; O53; N25; 330; Flow-of-funds analysis; Asset-liability matrix; Financial conglomerates (chaebol)